“Imitación por texturizado a carne de pulpa de gamitana ( colossoma macropomum) - Barrenechea Ramírez,Silvia (1999)
Is evaluated and processed fish Gamitana Colossoma. Macropomum coming of the areas fish of the Region San Martin Tarapoto located in the jungle high of the Peru. It was determined that the average length ranged between 28 and 35.5 cm. for the total length of the fish; in weight it averaged 530 grams and girth of 19 g/cm. The performance of ground pulpa1 which achieved 34,90% was analyzed. Also discussed the conditions of freshness that observed the Gamitana arriving at processing plants was of the highest quality (score 9) with a level of 15 BVN? 6 mgN/100 gr., and a PH of 6.5. The proximal chemical composition of pulp Gamitana presented the following composition: moisture 79,40%, protein 18.50%, 1.1%, carbohydrate 1%, ash fat 00/o. The summary of fatty acid formed fatty acids saturated levels of 32, 16%, % 34,94 monounsaturated fatty acids and polyunsaturated 31.85% acids; also be ruled out the presence of metal heavy or compounds toxic as the merc...